Ampharetidae (Annelida: Polychaeta) from Japanese waters. Part IV. Miscellaneous genera - Reuscher, M; Fiege, D; Imajima, M. (Journal of the Marine Biological Association of the United Kingdom, 2015)
In the fourth paper about Ampharetidae from Japan, we describe 12 species in seven genera. The genus Orochi gen. nov. and the eight species Amage ehlersi sp. nov., A. longitorus sp. nov., Glyphanostomum hesslei sp. nov., Lysippe nipponica sp. nov., Melinnopsis augeneri sp. nov., M. mcintoshi sp. nov., Orochi palacephalus gen. et sp. nov., and Samytha annenkovae sp. nov. are newly described. Orochi gen. nov. is characterized by the shovel-like prostomium, the high membrane, from which all four pairs of branchiae emerge and the presence of neuropodia of the abdominal type in the last thoracic unciniger. In the discussions of the remaining genera, we comment on the taxonomic changes suggested by Jirkov (2011). Furthermore, we provide a list of all Ampharetidae species that have been recorded from Japan.